2020
DOI: 10.4274/tjps.galenos.2018.35403
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Serotonergic Receptors and Nitric Oxide Systems in the Analgesic Effect of Acetaminophen: An Overview of the Last Decade

Abstract: Yeşim HAMURTEKİN, Ammar NOUILATI, Cansu DEMİRBATIR, Emre HAMURTEKİN* Asetaminofen yaygın kullanılan analjezik ve antipiretik bir ajandır. Reçetesiz verilebilen formülasyonlarının da mevcudiyeti sık kullanımını artırmıştır. Günümüze kadar asetaminofenin analjezik etki mekanizmasını inceleyen bir çok çalışma bulunmaktadır. Santral sinir sisteminde siklooksijenaz yolağını inhibe etmesinin yanında, opioiderjik, kannabinoiderjik, dopaminerjik, kolinerjik ve nitrerjik sistemler kadar, bulbospinal serotonerjik yolakl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Most of the time such drugs cause mild-to-moderate SS 19 21. Several painkillers such as aspirin, acetaminophen, tramadol and rofecoxib are known to increase serotonin levels in the brain 22–25. Tramadol is one of the most commonly prescribed drugs associated with SS 26.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the time such drugs cause mild-to-moderate SS 19 21. Several painkillers such as aspirin, acetaminophen, tramadol and rofecoxib are known to increase serotonin levels in the brain 22–25. Tramadol is one of the most commonly prescribed drugs associated with SS 26.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62][63][64][65][66][67][68][69][70][71] Nonetheless, the evidence was not conclusive regarding the contribution of serotonergic receptors to the paracetamol action. As an example, the involvement of 5-HT3 receptors has been discussed in humans, 62,70,[72][73][74] and experimental work in rodents with 5-HT3 receptor antisense oligonucleotides showed that they were not involved in the analgesic effect of paracetamol, while a tropisetron-sensitive receptor was. 74 However, investigations showed that p-aminophenol analgesic action was mediated by the bulbospinal serotonergic system, 18 which may suggest an involvement of this serotonergic system in the AM404 antinociceptive activity, as recently suggested.…”
Section: Dovepressmentioning
confidence: 99%
“…As an example, the involvement of 5-HT3 receptors has been discussed in humans, 62,70,[72][73][74] and experimental work in rodents with 5-HT3 receptor antisense oligonucleotides showed that they were not involved in the analgesic effect of paracetamol, while a tropisetron-sensitive receptor was. 74 However, investigations showed that p-aminophenol analgesic action was mediated by the bulbospinal serotonergic system, 18 which may suggest an involvement of this serotonergic system in the AM404 antinociceptive activity, as recently suggested. 63 Finally, if bulbospinal serotoninergic pathways seem to be involved in the analgesic effect of paracetamol or its metabolites, the exact nature of the spinal tropisetron-sensitive receptor involved in this effect remains to be elucidated.…”
Section: Dovepressmentioning
confidence: 99%
“…Paracetamol exerts a moderate analgesic effect by inhibiting the same cyclooxygenase (COX1) targeted by NSAIDs and aspirin [ 9 ]. At the central level, paracetamol also acts by increasing serotonin release [ 58 ]. Paracetamol blocks COX for its peroxidase catalytic activity rather than at the COX catalytic site.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%